PERANCANGAN SISTEM MONITORING PRAKTEK LAUT MENGGUNAKAN FRAMEWORK BOOTSTRAP PROGRAM KEAHLIAN PELAYARAN KAPAL NIAGA SMK WISUDHA KARYA KUDUS - Adhi Priyanto; Listiarini Edy Sudiati; Sugi Harsono (Electro Luceat, 2021)
SMK Wisudha Karya Kudus is one of the Vocational High Schools in Kudus Regency has several expertise programs, one of which is the Merchant Ship Sailing Expertise Program. Merchant Ship Nautical Competencies and Merchant Ship Engineering Competencies, which is under the Merchant Ship Sailing Expertise Program, using the curriculum of the Ministry of Education and Culture[1], the Ministry of Transportation[2] and International Maritime Organization[3], there is a ship training for a minimum of 12 months on a merchant ship which is carried out in semester VII. The process of registering and reporting on board training is currently still done manually which causes problems in the recording, reporting, monitoring and administration of documents. To overcome these problems in this study a web-based On Board Training Monitoring System was designed using Framework Bootstrap with the advantages of responsive display system both uses in browsers on computer and smartphone devices.